Differential Protection for Distributed Micro-Grid Based on Agent - ZHOU Bin; YING Li-ming; ZHU Yonggang (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The Micro-grid, even though not a replacement of the conventional centralized power transmission grid, plays a very important role in the success of rapid development of renewable energy resources technologies. Due to the facts of decentralization, independence and dynamic of sources within a Micro-grid, a high level automation of protection is a must. Multi-Agent system as a approach to handle distributed system issues has been developed. This paper presents an MAS based differential protection method for distributed micro-grid. The nodes within a micro-grid are divided into primary and backup protection zones. The agents follow predefined rules to take actions to protect the system and isolate the fault when it happens. Furthermore, an algorithm is proposed to achieve high availability in case of Agent itself malfunction. The method is using Matlab for simulation and shows it satisfies relay protection in terms of the selectivity, sensitivity, rapidity and reliability requirements. DOI: http://dx.doi.org/10.11591/telkomnika.v11i5.2497